PRINCIPLES OF SELECTION OF CHILDREN WITH HEARING DEFECTS INTO SPECIAL EDUCATIONAL INSTITUTIONS - Kahramonova Zebuniso Raufjonovna (TADQIQOTLAR, 2026)
Abstract. This article provides information on the principles of selection of children with hearing impairment to special educational institutions. The practice of special schools for hearing impaired children has clearly confirmed that teaching children with hearing impairments from different groups together does not produce effective results.